Associations of trauma exposure and post-traumatic stress disorder with the activity of the renin–angiotensin–aldosterone-system in the general population. Issue 5 (18th June 2018) - Terock, Jan; Hannemann, Anke; Janowitz, Deborah; Freyberger, Harald J.; Felix, Stephan B.; Dörr, Marcus; Nauck, Matthias; Völzke, Henry; Grabe, Hans J.
Abstract: Background: Previous studies suggested that exposure to traumatic events during childhood and adulthood and post-traumatic stress disorder (PTSD) are associated with a dysregulation of different neuroendocrine systems. However, the activity of the renin–angiotensin–aldosterone-system (RAAS) in relation to trauma/PTSD has been largely neglected. Methods: Traumatization, PTSD, and plasma concentrations of renin and aldosterone were measured in 3092 individuals from the general population. Subgroups according to the status of traumatization ('without trauma'; 'trauma, without PTSD', 'PTSD') were formed and compared regarding renin and aldosterone concentrations. Additionally, we calculated the associations between the number of traumata, renin, and aldosterone concentrations. Finally, associations of PTSD with renin/aldosterone levels were controlled for the number of traumata ('trauma load'). Results: Levels of renin, but not aldosterone, were increased in traumatized persons without PTSD ( p = 0.02) and, even stronger, with PTSD ( p < 0.01). Moreover, we found a dose–response relation between the number of traumata and renin levels ( β = 0.065; p < 0.001). Regression analyses showed PTSD as a significant predictor of renin ( β = 0.38; p < 0.01). This effect was only slightly attenuated when controlled for trauma load ( β = 0.32; p < 0.01). Conclusions: Our results suggest that traumatization has lasting and cumulative effects on RAAS activity. Finding elevated renin levels in PTSD independent from trauma load supports the concept of PTSD as a disorder with specific neuroendocrine characteristics. Alternatively, elevated renin levels in traumatized persons may increase the risk for developing PTSD. Our findings contribute to explain the relationship between traumatic stress/PTSD and physical disorders.